Spatial and temporal variability of cyanobacteria in two subtropical reservoirs: community composition, molecular and cyanotoxin analyses - Moraes, Munique de Almeida Bispo (2020)
Toxic cyanobacteria in public water supply reservoirs represent a serious health risk since they can release cyanotoxins into the water. Among the cyanotoxins produced by cyanobacteria are microcystin (MC - hepatotoxin) and saxitoxin (STX - neurotoxin). Considering that these two toxins are recurrent in Brazilian water systems, the main objective of this doctoral research was to assess the effect of environmental variables on the composition, abundance and toxicity of cyanobacterial communities in the subtropical reservoirs Itupararanga and Lobo (São Paulo State, Brazil) in order to generate information to help on the proper monitoring of these aquatic ecosystems and minimize the risks to the public health. Water samples were collected in the riverine and dam zones from both reservoirs at two depths in May, August and October 2017 and January 2018. Occurrences of potentially saxitoxin- and microcystin- producing cyanobacteria were determined by microscope analysis and quantitative PCR assays through the detection of sxtA and mcyE genes, respectively. Concentrations of MC and STX were measured through ELISA. Presence of microcystin- and saxitoxin-producing cyanobacteria in both reservoirs was confirmed by the detection of mcyE and sxtA genes, respectively. Among the identified genera of cyanobacteria, Aphanizomenon, Geitlerinema, Phormidium and Raphidiopsis were considered as the potential producers of MC and STX in the reservoirs. The cyanobacterial biovolume in Itupararanga reservoir was higher than in Lobo reservoir. In January 2018, the cyanobacterial biovolume in the dam zone of Itupararanga reservoir constituted more than 60% of total phytoplankton biovolume, and the most dominant cyanobacterium was Raphidiopsis raciborskii. In Lobo reservoir the highest contribution of cyanobacteria was 12% in the dam zone in May 2017. Microcystin and saxitoxin concentrations were detected in the two subtropical reservoirs. For most of the study period, cyanotoxin concentrations were below the maximum limit allowed by the Ministry of Health for public water supply. Nevertheless, MC concentrations exceeded the limit allowed in drinking water for human consumption in two samples (May 2017 in the dam zone of Lobo reservoir), posing a risk to the local people. The occurrence of toxins in the reservoirs was influenced by different environmental variables, but the results showed that nutrients played an important role in their occurrence since the nitrogen and phosphorus limitation appeared to be responsible for the increase in toxin production. The mcyE and sxtA genes were directly correlated with microcystin and saxitoxin concentrations in both reservoirs, suggesting that qPCR associated with ELISA/LC-MS can be used as a fast and reliable tool to monitor the occurrence of toxic cyanobacteria in environmental samples.